Expression and Refolding of the Plant Chitinase From Drosera capensis for Applications as a Sustainable and Integrated Pest Management - Sinelnikov, Igor G.; Siedhoff, Niklas E.; Chulkin, Andrey M.; Zorov, Ivan N.; Schwaneberg, Ulrich; Davari, Mehdi D.; Sinitsyna, Olga A.; Shcherbakova, Larisa A.; Sinitsyn, Arkady P.; Rozhkova, Aleksandra M. (Frontiers in Bioengineering and Biotechnology, 2021)
Recently, the study of chitinases has become an important target of numerous research projects due to their potential for applications, such as biocontrol pest agents. Plant chitinases from carnivorous plants of the genus Drosera are most aggressive against a wide range of phytopathogens. However, low solubility or insolubility of the target protein hampered application of chitinases as biofungicides. To obtain plant chitinase from carnivorous plants of the genus Drosera in soluble form in E.coli expression strains, three different approaches including dialysis, rapid dilution, and refolding on Ni-NTA agarose to renaturation were tested. The developed «Rapid dilution» protocol with renaturation buffer supplemented by 10% glycerol and 2M arginine in combination with the redox pair of reduced/oxidized glutathione, increased the yield of active soluble protein to 9.5 mg per 1 g of wet biomass. A structure-based removal of free cysteines in the core domain based on homology modeling of the structure was carried out in order to improve the soluble of chitinase. One improved chitinase variant (C191A/C231S/C286T) was identified which shows improved expression and solubility in E. coli expression systems compared to wild type. Computational analyzes of the wild-type and the improved variant revealed overall higher fluctuations of the structure while maintaining a global protein stability. It was shown that free cysteines on the surface of the protein globule which are not involved in the formation of inner disulfide bonds contribute to the insolubility of chitinase from Drosera capensis. The functional characteristics showed that chitinase exhibits high activity against colloidal chitin (360 units / g) and high fungicidal properties of recombinant chitinases against Parastagonospora nodorum. Latter highlights the application of chitinase from D. capensis as a promising enzyme for the control of fungal pathogens in agriculture.